Exploring the social factors influencing voting behavior in 2019 National Assembly elections in Gombe State, Nigeria - Tal, Mohammed Kwarah; Ismail, Mohd Mahadee; Ku Shamsu, Ku Hasnita; Adnan, Zatul Himmah (Human Resource Management Academic Research Society, 2024)
Gombe state is a diverse society where social factors significantly influence voting behavior. Voting behavior reflects a society’s political culture and it is concerned with factors that influence voting choices. Therefore, exploring the social factors influencing voting behavior in the 2019 elections is crucial in understanding how the politicians manipulated social forces to achieve their political interests. The paper applies classical liberal democracy theory and a qualitative case study design. Purposive and snowballing selection of informants was conducted through online Zoom in-depth interviews. A thematic approach was used in data analysis. Findings reveal politicians intimidated voters by manipulating ethno-religious sentiment, abject poverty, and low literacy/political education levels, to significantly influence voting behavior to their advantage. The paper recommends government and NGOs should give utmost priority to improving literacy rate, political education level, and poverty alleviation through skills acquisition. There should be zero tolerance for corruption and strict enforcement of the rule of law, where sacred cow treatment is discouraged. Furthermore, the paper recommends farther research in the study area covering the whole of Nigeria using quantitative design to enable for the enrichment of the literature on electoral matters, political behavior, and the influence of social factors in national elections.